Broad host range of human T-cell leukemia virus type 1 demonstrated with an improved pseudotyping system. - Sutton, R E (1996)
Studies of human T-cell leukemia virus type 1 (HTLV-1) have been hampered by the difficulty of achieving high cell-free and cell-associated infectious titers. Current retroviral pseudotyping systems using the HTLV-1 envelope generate titers of less than 200 infectious particles per ml. We describe here an improved system for pseudotyping using a defective human immunodeficiency virus (HIV) type 1 genome in combination with HTLV-1 env in 293T producer cells. Introduction of additional copies of rev and treatment of cells with sodium butyrate resulted in a cell-associated titer of 10(5)/ml and cell-free titers of greater than 10(4)/ml . By using this system, we found that the host range of HTLV-1 is even greater than previously suspected. Earlier studies which assigned a chromosomal location for the HTLV-1 receptor may therefore reflect cell-to-cell variation in receptor number rather than the absolute presence or absence of a receptor. The generation of higher-titer HIV(HTLV-1) may facilitate identification of the cellular receptor and investigations of the pathophysiology of HTLV-1 infection.